Analisis Strategi Pemasaran Online dan Offline Koperasi Batik Ciwaringin Cirebon dalam Menjangkau Pasar Lokal Hingga Internasional - Mira Yuli; Dini Selasi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This Study aims to analyze the online and offline marketing strategies carried out by the Anugerah Batik Ciwaringin Cooperative in Cirebon. Its marketing is carried out through social media such as Instagram and Whatsapp online, and through offline means such as direct sales, batik training, and participating in batik exhibitions.Interestingly, this Cooperative, although not yet utilizing the marketplace, has succeeded in reaching consumers as far as Singapore and Australia. The method in this study is a descriptive qualitative methode with a case study approach. Data were obtained from interviews and direct observations at the Anugerah Batik Ciwaringin Cooperative with the results of the study showing that the marketing strategy of this cooperative is still simple but consistent in direct promotion so that it is able to expand market reach to foreign countries. The Anugerah Batik Ciwaringin Cooperative received recognition from Bank Indonesia for its contribution to local economic development. This international market success demonstrates that the synergy of cultural education and tradisional consumer loyalty can effectively replace modern digital platforms to increase regional product salaes.